(untitled) (Academia Journal of Medicine, 2020)
Background: Lipid abnormalities in patients with diabetes are often phrased as “diabetic dyslipidemia”. The aim of the study was to evaluate the lipid profiles of patients with type-2 diabetes mellitus. Subjects and Methods: the subjects who were enrolled in this study were diabetic patients. For the study, a total of 150 diabetic patients with a history of diabetes for 10 years were arbitrarily chosen and scrutinized for dyslipidemia. Patients with other diseases and metabolic disarray were barred from the study. The patients were selected on an indiscriminate base and detailed case history was measured with all appropriate clinical checks. Results: Total 140 diabetic patients with a mean age of 49.98 ± 13.3 years were included in the study. The mean FBS of study participants was 189.78± 55.65 mg/dl. Mean triglycerides level was 203.59 ± 84.48mg/dl. Out of the total 150 patients, borderline high cholesterol (200-239 mg/dl) and high cholesterol (≥240 mg/dl) level were 29 (19.3%) and 22 (14.6%) respectively. Out of 150 subjects, 37(24.6%) had borderline high triglyceride (150-199 mg/dl) while 61 (40.6%) had high triglyceride (200-249 mg/dl) level. Conclusion: Hyperlipidemia is the most frequent snag of diabetes mellitus and it can prompt patients to precipitate atherosclerosis and microvascular difficulty. Good glycemic control can avert the advances and succession of usual lipid irregularity in diabetes like heightened triglycerides, LDL, serum cholesterol and low HDL.